1996
DOI: 10.1021/la960320p
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization of N-Alkylpyridinium Ions in Anionic Nematic Lyomesophases

Abstract: Deuterium quadrupole splittings from the aromatic ring of a series of linear N-alkylpyridinium-d 5 ions, with alkyl chains from 1 to 16 carbon atoms, were measured using 2H-NMR spectroscopy. The pyridinium ions, 10% deuteriated in the aromatic ring, were dissolved in nematic anionic lyomesophases prepared from sodium decyl sulfate (SDS) and cesium decyl sulfate (CsDS). With these splittings, the two order parameters that completely describe the average orientation of the aromatic ring with respect to the magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The alkylpyridinium ions have high affinity for negatively charged aggregates [23,24] and the probability of contact between fluorophore and quencher in the presence of SDS and SDS-PEO micelles is increased, enhancing the quenching compared to PBS medium (Table 3). In those micelles the highest K SV values for ACTH(1-24) fluorescence quenching was observed for N-ethylpyridinium (NEP + ), indicating that its Trp residue is located near to the surface of the aggregates, the preferential location of NEP + .…”
Section: Steady State Fluorescence Quenchingmentioning
confidence: 99%
See 2 more Smart Citations
“…The alkylpyridinium ions have high affinity for negatively charged aggregates [23,24] and the probability of contact between fluorophore and quencher in the presence of SDS and SDS-PEO micelles is increased, enhancing the quenching compared to PBS medium (Table 3). In those micelles the highest K SV values for ACTH(1-24) fluorescence quenching was observed for N-ethylpyridinium (NEP + ), indicating that its Trp residue is located near to the surface of the aggregates, the preferential location of NEP + .…”
Section: Steady State Fluorescence Quenchingmentioning
confidence: 99%
“…Several N-terminal segments of ACTH were found to have hormonal activities and specific receptor binding properties: ACTH binds to steroidogenic receptors, while ACTH(1-10) was found to bind preferentially to central nervous receptors. The fragment ACTH (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) is an antagonist for steroidogenesis without any agonist properties [10]. ACTH may enhance memory cytotoxic responses through a combination of mechanisms such as direct cell alterations or synergy with regulatory cytokines [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were recrystallized three times from ethyl acetate/ethanol solutions before use. SDS was prepared and purified using a previously reported methodology [13]. Anhydrous NaCl, NaBr and Na 2 SO 4 were purchased from Aldrich and used without further purification.…”
Section: Nmr Samples and Spectramentioning
confidence: 99%
“… The use of 2 H-NMR quadrupole splittings is possibly one of the simplest methods to estimate molecular order parameters and, from these, to infer the average orientation, and sometimes the location, of guest molecules dissolved in anisotropic solutions. Recently, using 2 H-NMR spectroscopy, we have measured the two order parameters that completely describe the average orientation and have been able to infer the location of the aromatic ring in a series of linear N -alkylpyridinium- d 5 ions, dissolved in cationic and anionic nematic lyotropic liquid crystals. , All the mesophases studied by us were type II systems . We found that addition of small amounts of pyridinium ions to liquid crystal solutions made from hexadecylpyridinium chloride (HDPyCl), tetradecyltrimethylammonium bromide (TDTMABr), and cesium decyl sulfate (CsDS) had an appreciable effect on the mobility of these interfaces.…”
Section: Introductionmentioning
confidence: 99%